Low-Cost Android Based Tele-Monitoring System for Body Temperature Measurement - Özcan, Ahmet Remzi; Mert, Ahmet (Bursa Teknik Üniversitesi, 2021)
The increasing number of pandemic issues require to pay attention to health conditions and social distance. The explicit sign of COVID-19 is body fever. It is a simple and affordable detection method when compared to other blood tests. However, it is required to be physically close to a visitor to measure body temperature. For this reason, we have designed and developed a low-cost microprocessor measurement system with an infrared non-contact temperature sensor, and a Bluetooth for sending to long distance. Android application has been developed to read and set the alarm function using a smart telephone or a tablet far from the visitors. With the help of these circuit and application designs, body temperatures can be checked from long distance considering the pandemic situations. The printed circuit of the microcontroller, Bluetooth, sensor, and light-dependent resistor (LDR) triggering are manufactured, and the software of the controller and the application are integrated and tested successfully.
200COVİD05.
Keywords: Engineering; Mühendislik